New Developments in Anxiety Disorders 2016
DOI: 10.5772/66117
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Mental Disorders in Anxiety Disorders: Genetic Aspects of Bipolar Disorders and of Ethnicity

Abstract: Anxiety disorder (AD) is commonly comorbid with other mental illness. It could be a state or trait, controversially. Evidence for an association between alcoholism and anxiety has emerged from clinical studies of patients with alcoholism, and those of patients with anxiety disorders. Alcohol dependence (or abuse) as well as bipolar disorder (BP) is usually comorbid with anxiety disorder and/or depressive disorder, which often coexist and are difficult to distinguish from one another. However, in Han Chinese po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 121 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…Ethnic differences have also been noted in epidemiological studies[74]. Notably, some reviews have found lower rates of anxiety disorders among Asian patients with BD; genetic differences have been proposed to account for this finding[69,122,135].…”
Section: Demographic Correlates Of Anxiety Disorder Comorbidity In Bdmentioning
confidence: 96%
See 4 more Smart Citations
“…Ethnic differences have also been noted in epidemiological studies[74]. Notably, some reviews have found lower rates of anxiety disorders among Asian patients with BD; genetic differences have been proposed to account for this finding[69,122,135].…”
Section: Demographic Correlates Of Anxiety Disorder Comorbidity In Bdmentioning
confidence: 96%
“…Conversely, only a few studies have been unable to find this relationship between anxiety disorders and SUDs in BD[9,28,113]. The presence of a combination of anxiety disorders and SUDs in BD not only complicates the diagnosis, but also impairs treatment response and can lead to a more severe course of illness and increased suicidal risk[10,17,27,69,154]. Apart from associated SUD comorbidity, anxiety disorders in BD have also been linked with other comorbid conditions such as attention deficit hyperkinetic disorders, eating disorders, and a range of personality disorders[9,14,18,22,42].…”
Section: Clinical Correlates Of Anxiety Disorder Comorbidity In Bdmentioning
confidence: 99%
See 3 more Smart Citations